Method of Moving Region Detection for Static Camera - Goel, Pravesh Kumar; Kotak, Paresh P.; Gupta, Amit (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
The moving object detection from a stationary video sequence is a primary task in various computer vision applications. In this proposed system; three processing levels are suppose to perform: detects moving objects region from the background image; reduce noise from the pixels of detected region and extract meaningful objects and their features (area of object, center point of area etc.). In this paper; background subtraction techniques is used for segments moving objects from the background image, which is capable for pixel level processing. Morphology operation (Erosion and dilation) are used to remove pixel to pixel noise. In last level, CCL algorithm is used for sorts out foregrounds pixels are grouped into meaningful connected regions and their features.